1975
DOI: 10.1111/j.1476-5381.1975.tb07586.x
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Anoxia on the Ventricular Fibrillation Threshold in the Rabbit Isolated Heart

Abstract: The ventricular fibrillation threshold (VFT) was measured in the isolated heart of the rabbit perfused via the aorta with McEwen's solution at 37° C by applying a single 10 ms pulse of current during the vulnerable period of late systole. The arrhythmia induced was either fibrillation or a rapid tachycardia. Gassing the McEwen's solution with 5% CO2 in N2 (anoxia) instead of with carbogen caused a negative inotropic and chronotropic effect and significantly lowered the VFT. Although anoxia releases noradrenali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1978
1978
2017
2017

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…Serum potassium level was normal in both groups. Hypoxia, the most important causative factor of CA in patients with CP, exerts its effect on action potentials in the heart muscle [18] sinoatrial nodal cells, conducting system [19], mesencephalic ret icular formation [20], and the central ner vous system [21] by reducing the ventricu lar fibrillation threshold [22]. Our study showed that the CA were frequent al though supplemental oxygen was given and patients were sufficiently oxygenated.…”
Section: Discussionmentioning
confidence: 71%
“…Serum potassium level was normal in both groups. Hypoxia, the most important causative factor of CA in patients with CP, exerts its effect on action potentials in the heart muscle [18] sinoatrial nodal cells, conducting system [19], mesencephalic ret icular formation [20], and the central ner vous system [21] by reducing the ventricu lar fibrillation threshold [22]. Our study showed that the CA were frequent al though supplemental oxygen was given and patients were sufficiently oxygenated.…”
Section: Discussionmentioning
confidence: 71%
“…Since a high concentration of free fatty acids (FFA) cause an increased demand for oxygen (Mj0s, 1971;Kjekshus & Mj0s, 1972) they would be expected to increase the degree of hypoxia so that it would approach that of the anoxic state. Since anoxia is more arrhythmogenic than hypoxia in so far as it lowers the VAT more (Murnaghan, 1975), then FFA when combined with hypoxia would be expected to increase the incidence of an arrhythmia.…”
Section: Discussionmentioning
confidence: 99%
“…Ischemia and hypoxia during cardioplegic arrest result in respiratory chain failure and might finally initiate cell death (Luo et al, 2015 ). Hypoxic conditions during cardioplegia as well as reperfusion injury may result in reduced contractile function and promote arrhythmia, a situation in which catecholamine treatment is usually necessary with additional antiarrhythmic medication or electrical defibrillation and which has a negative impact on patient outcome (Murnaghan, 1975 ; Casthely et al, 1994 ).…”
Section: Introductionmentioning
confidence: 99%